Study of PUBG Addiction Level Among University Students - Djafar, Imran; Johanis M, Andrew Ridow; Arifin, Suci Ramadhani (SAINTEKBU, 2023)
PlayerUnknown's Battleground (PUBG) is one of the most popular and successful games globally and become very popular among the youths in recent years. The number of active players continues to increase globally, even reaching 100 million players every month. Of this number, the second country in the world that has monthly active players is Indonesia. Recent academic studies and statistical research reveal that game addiction among college students has shown an increasing trend, and will likely increase in the future as well. This study was conducted to find out the level of addiction of PUBG especially for at the Dipa Makassar University students. PUBG Addiction Test (PAT) was used to measure the level of PUBG addiction among young adolescents. The results of this study indicate that most of the respondents, or 46.0% of respondents belong to the category of low-level addiction, followed by those who are in the moderate-level category (44.9%). Respondents who are included in the high level category are only a small portion of 8.9%.